Fragile Interpersonal Relationship in Tacit Knowledge Sharing: How Workplace Friendship Fails Under Competition and Functional Similarity - Wu, Chunlin; Hu, Xiao; Guo, Xuanhao; Ning, Xin; Hui, Chun (Production and Operations Management, 2026)
In the competitive landscape of modern business, tacit knowledge (TK) sharing has emerged as a critical enabler of innovation and transformation, particularly within the realm of operations management. In this context, the efficient flow of TK is essential for optimizing processes, promoting technology development, and sustaining competitive advantage. While the role of workplace friendship in facilitating TK sharing has been well-documented, there is a common misconception that close personal relationships alone suffice for effective knowledge transfer. However, in the complex dynamics of operational environments, these relationships can be unexpectedly fragile and prone to disruption. Even employees with strong workplace friendships may encounter inevitable challenges such as competition over limited resources, conflicts of interest, and diminished incremental benefits of knowledge exchange among functionally overlapping colleagues. Grounded in social information processing (SIP) theory, this study proposes a moderated mediation model and explores the negative moderating effects of competitive climate and functional similarity on the relationship between workplace friendship and TK sharing and how these factors subsequently impact innovation performance. Through a mixed-method design, including a main field study and a supplementary experiment involving 1,809 participants across various industries, our findings underscore that the positive association between workplace friendship and TK sharing will be diminished or even dissolved when employees perceive higher levels of competitive climate and functional similarity. By adopting a SIP perspective, this research elucidates how contextual factors in operational environments can overshadow the influence of workplace friendship on TK sharing. It also reveals the intricate interplay (i.e., mutual reinforcement) between the attitudes of TK holders and recipients, which is crucial for ensuring the seamless exchange of knowledge that drives operational excellence in highly competitive workplaces. These insights are vital for operations managers aiming to cultivate workforce diversity, regulate peer competition, inspire employee enthusiasm and engagement, and initiate cross-functional technology development projects. Such strategies foster effective and sustainable TK sharing, ultimately contributing to superior innovation performance in operational settings.